Chemotaxonomic importance of diarylheptanoids and phenylpropanoids in Saxifraga tangutica (Saxifragaceae). (June 2017) - Dang, Jun; Jiao, Li-jin; Wang, Wei-dong; Pei, Jin-jin; Tao, Yan-duo; Shao, Yun; Mei, Li-juan; Wang, Qi-lan; Zhang, Li
Abstract: A phytochemical investigation of Saxifraga tangutica led to the isolation of 11 compounds, including eight diarylheptanoids (1 –6, 10 and11 ) and three phenylpropanoids (7 –9 ). The chemical structures were established by extensive analysis of their MS and NMR spectroscopic data or comparison with literature data. In the present research, we report the isolated compounds1 –11, for the first time, in the species S. tangutica . Moreover, compounds1, 2 and4 –11 have not been reported from any species in Saxifragaceae family. Furthermore, we discuss the chemotaxonomic significance of the isolated compounds. Highlights: Eight diarylheptanoids and three phenylpropanoids have been isolated from Saxifraga tangutica. Compounds1 –11 are firstly reported in the species Saxifraga tangutica. Compounds1, 2 and4 –11 are firstly isolated from genus Saxifraga or family Saxifragaceae.